Research on anthropometric factors and balance stability of figure skaters - Yordanova, T. (Journal of Applied Sports Sciences, 2020)
One of the characteristics of modern figure skating is the progressive complication of the competitive programs. This process develops, in particular, in the way of athletes` mastery of complex coordination elements and compounds of a rotating nature, which appear to be a strong irritant to the vestibular analyzer. The aim of the present study was to investigate the influence of anthropometric factors on the balance stability of female figure skaters. The study`s tasks, which are divided into three groups, as well as the subject and object of the study, are presented. The used methods are described. The methodology of the study is separated and detailed. Also, the different abilities of the body for balance resistance, in various motor actions are described. One of the main used methods is called Stabilometry. The design of the study is followed. The results are visualized in six tables, which are illustrated by five figures. In conclusion, the dependence of Anthropometric status is noted in accordance with the height and length of the lower limbs and the width of the pelvis. The dynamic retention of the balance in landing position is more effective than the static balance in the Romberg posture, which is explained by the specificity of the sport figure skating. There is a worsening of the balance in the increase of anthropometric parameters - height, weight and chest circumference. Balance fluctuations in the Romberg position are significantly dependent on the weight and chest circumference, while the height of the skaters affects the balance - with increasing amplitude there is also an increase in balance fluctuations in the landing position after a jump, i.e. the balance is unstable, which is explained by a higher placement of the center of gravity of the body.